Dialog Etika: Immanuel Kant Dan Al-Ghazali Tentang Kewajiban Moral - Yanti, Riska; Juhardi, Juhardi (JENTRE, 2025)
This study aims to explore the common grounds and fundamental differences between Immanuel Kant’s deontological ethics and al-Ghazali’s ethical thought, particularly concerning the concept of moral duty. Kant emphasizes the categorical imperative as the universal and rational foundation of morality, while al-Ghazali grounds moral obligation in obedience to divine law and the purification of the soul as a path to ultimate happiness in the hereafter. Employing a qualitative library research approach, this paper examines kant’s rational morality, situating both within a constructive philosophical dialogue. The analysis  reveals that despite their distinct foundations autonomous reason in the Western tradition and divine revelation in the Islamic tradition both converge on the affirmation of moral duty as the basis of ethical life. This study contributes to comparative ethical discourse by opening the possibility of integrating rational and religious ethics in fostering a more comprehensive moral awareness.